Abordajes psicoanalíticos a inquietudes sobre la subjetividad III - Orejuela Gómez, Johny Javier (Señales, 2016)
The paradigms of training, integration and quality that the university must embody, together with the acceleration of technological, demographic, urban, environmental, social, productive and economic processes, create the need to interpret extension in its broadest sense and involve it in the most diverse aspects of linking with society and the environment not only by transferring, but also - and fundamentally - by listening. It is not enough to open the doors of the university; nowadays, it is necessary to go out and become part of the community. This book, in its three thematic axes: psychoanalysis, discomfort and culture; clinical stakes, and psychoanalysis, science and research, is a testimony that the research line "Intersections of psychoanalysis" is concerned and concerned with community issues and from there questions the articulation between psychoanalysis, science and research. Psychoanalytic approaches to concerns about subjectivity is the production of a line of research, which leads us to congratulate all its authors for the fact of sustaining the discomfort of the implication it entails: to put a question to work under a condition: he who asks does not rest! If one responds to the ethics of psychoanalysis, the researcher sustains the discomfort of enduring it.